2007
DOI: 10.1007/bf03181897
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory thermal structures in a reattaching jet flow

Abstract: Spatially varying surface temperature oscillations in a nominally steady reattaching slot jet at a Reynolds number (Re) of 5000 are analyzed using Proper Orthogonal Decomposition (POD) for two nozzle-to-surface spacings, and three exit openings of the nozzle. The surface temperature data in these experiments were recorded using infrared thermography at a frequency of 20 Hz along two selected lines on the impingement surface corresponding to geometrically similar and dissimilar regions within the reattachment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recent investigations show that the potential of IRT can be dramatically enhanced by filtering the measurement data sets using proper orthogonal decomposition (POD). For example, Narayanan (2007) applied this methodology to study the modes of temperature fluctuations of slot jet impingement by filtering IRT data with first 15 POD modes. Ranc et al (2015) demonstrated improvements in the signalto-noise ratio of IRT measurements of a thermomechanical phenomenon by selecting physically admissible thermal modes from POD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations show that the potential of IRT can be dramatically enhanced by filtering the measurement data sets using proper orthogonal decomposition (POD). For example, Narayanan (2007) applied this methodology to study the modes of temperature fluctuations of slot jet impingement by filtering IRT data with first 15 POD modes. Ranc et al (2015) demonstrated improvements in the signalto-noise ratio of IRT measurements of a thermomechanical phenomenon by selecting physically admissible thermal modes from POD.…”
Section: Introductionmentioning
confidence: 99%